John Locke’s Conception of the Social Contract and Its Relations to the Term Limits in Governance - Mohammad Fajar Pramono; Mohamad Latief; Randa Jaelani (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. In political discourse, many theories have emerged regarding the idealization of government, state, and leadership. However, existing theories have not fully succeeded in realizing an ideal government, state, or leader. In fact, some theories tend to emphasize the absolutism of power that leads to authoritarian leaders. This study will analyze John Locke's version of the social contract theory and relate it to the issue of the periodization of the leadership term in a government. The method used is a literature study with a correlation analysis approach. The results of the study show that the social contract theory in John Locke's thinking has a close relationship with the existence of the periodization of the term of office or leadership in government. If this periodization does not apply, it will give rise to a tendency to commit corrupt acts on the mandate held. There are several important points to consider in re-examining the dynamics and processes of leadership in government; 1) upholding the sovereignty of the people; 2) the need for regeneration of the leadership relay; 3) anticipation of abuse of power; and 4) the need to guarantee the prosperity and welfare of citizens. Keywords: John Locke, Social Contract, Term Limits, Governance. Abstrak. Dalam diskursus politik, banyak teori yang muncul mengenai idealisasi pemerintahan, negara, dan kepemimpinan. Namun, teori-teori yang ada belum sepenuhnya berhasil mewujudkan pemerintahan, negara, atau pemimpin yang ideal. Bahkan, beberapa teori cenderung menekankan pada absolutisme kekuasaan yang berujung pada pemimpin yang otoriter. Penelitian ini akan menganalisis teori kontrak sosial versi John Locke dan mengaitkannya dengan isu periodisasi masa kepemimpinan dalam sebuah pemerintahan. Metode yang digunakan adalah studi literatur dengan pendekatan analisis korelasi. Hasil penelitian menunjukkan bahwa teori kontrak sosial dalam pemikiran John Locke memiliki keterkaitan yang erat dengan adanya periodisasi masa jabatan atau kepemimpinan dalam pemerintahan. Jika periodisasi ini tidak berlaku, maka akan menimbulkan kecenderungan untuk melakukan tindakan koruptif atas amanah yang diemban. Ada beberapa poin penting yang perlu diperhatikan dalam menelaah kembali dinamika dan proses kepemimpinan dalam pemerintahan, yaitu: 1) menjunjung tinggi kedaulatan rakyat; 2) perlunya regenerasi estafet kepemimpinan; 3) antisipasi penyalahgunaan kekuasaan; dan 4) perlunya menjamin kemakmuran dan kesejahteraan warga negara. Kata Kunci: John Locke, Social Contract, Periodesasi Jabatan, Pemerintahan.